Faktor-Faktor Lingkungan dan Perilaku Yang Berhubungan dengan Kejadian Filariasis di Kabupaten Bangka Barat - Nasrin, Nasrin; Setiani, Onny; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2009)
ABSTRACT Background : West Bangka district is one of the endemic areas of filariasis in Indonesia. In  2007, It was found about 36 chronic cases of filariasis. The high incidence of  filariasis cases in West Bangka Regency  was caused by many factors in  the environment,  such as swamp and ponds or  hole in tin mining area which was flooded when raining or in rainy seasons.  The aim of this research was to find out  factors related to the filariasis incidence in West Bangk Regency. Method : It was an observational research using case control design. The subjects of this research was devided in  two groups: cases and controls with 37 subjects of each group. The variables assessed in this research including  physical factors (swamp / pool), Biological (water plants, fish/animal predators) for  the environmental factors and education, job and income as socioecomic factor Behavioural  factors were  consisted of  hanging out habit  at night, wearing clothes to protect mosquitoes bite that might influenced the filariasis incidence in West Bangk Regency. The data were analyzed using multiple logistic regression  at 5%  level of significance. Result : The result of this research showed that there were seven variabels asrisk factors of  filariasis incidence in West Bangka Regency,including: respondent’s job  with OR = 3,695, respondent’s income level  with OR = 4,2,  the existence of swamp OR = 3,151, habit of using mosquito repellent with OR = 5,063, respondent’s knowledge about filariasis OR = 4,259, respondent’s knowledge about filariasis infection with OR =3,571 and respondent’s knowledge about filariasis prevention OR= 3,73. Conclusion : Environmental and behavioural factor were related to filariasis incidence in West Bangka District. It was recommended to improve those factors by implementing health promotion intensively. Keyword   : Filariasis, enviromental and behavioral factors, West Barat District.